Pengembangan Sistem Forecasting Penjualan Pada Aplikasi Point of Sales Menggunakan Metode Trend Least Square - Ita Yulianti; Ami Rahmawati (Jurnal Larik: Ladang Artikel Ilmu Komputer, 2022)
The use of cash register as evidence of technology utilization in business activities is not enough to help the sustainability of a business, because it has not fully controlled data collection, especially in terms of information about the development of income and inventory planning. Therefore, for the sake of the business sustainability, the strategy is needed, one of which is to build a system that can manage the transaction process equipped with sales forecasting features that can display product predictions according to market needs. To build a system of data collection techniques, the waterfall system development model and the implementation of the Least Square trend method. Of the three research methods that are applied, the contribution produced is in the form of a desktop-based Point of Sales (POS) system with Java programming languages equipped with additional features, namely sales prediction. Based on the application of the system it is proven that the use of the Trend Least Square method is very appropriate to use because it can display the prediction results of sales for the coming period with predictive error rates of only 0.0067% and this system also helps optimize service activities to customers and can help sales management in terms of Provision of products.